An Interview with APPLE Lecture Speaker Dr. Walt Wolfram - Jessica Coombs; Miriah Ralston; Cicely Rude (Studies in Applied Linguistics & TESOL, 2023)
On March 3, 2023, the Studies in Applied Linguistics and TESOL (SALT) journal interviewed Dr. Walt Wolfram, an invited speaker for the 2023 APPLE Lecture Series hosted by the Applied Linguistics and TESOL Program at Teachers College, Columbia University.